แผนกำหนดการใช้ยาแวนโคมัยซินในผู้ป่วยวิกฤต โดยใช้การวิเคราะห์เภสัชจลนศาสตร์ประชากร และการจำลองเภสัชจลนศาสตร์/เภสัชพลศาสตร์ - ภูมิปรัชญ์ แก้วมหานิล (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
Objectives: The aims of this study were to determine population pharmacokinetic parameters of vancomycin and to evaluate the appropriate vancomycin dosage regimens in critically ill patients by PK/PD index simulation. Methods: The retrospective analytical study was conducted from January 2014 to December 2016 in critically ill patients undergoing routine therapeutic drug monitoring of vancomycin. Population pharmacokinetic modeling was analyzed using nonlinear mixed effect model (NONMEM) program. Monte-Carlo Simulation based on the target of PK/PD index (AUC24h/MIC ≥ 400) was conducted to calculate the probability of target attainment (PTA) and the cumulative fraction of response (CFR) of vancomycin dosage regimens. Results: Population pharmacokinetic modeling was performed using the data from 398 plasma concentration samples. Creatinine clearance, comorbidity with diabetes mellitus and sepsis with unknown sources were found significantly influence CL whereas V of vancomycin showed significant dependence on patient serum creatinine and gender. The estimated mean values from the final model were CL=3.63 L/h and V=106.8 L. The simulation data showed that the appropriate initial dosing was 20 mg/kg of loading dose then 20 mg/kg/day of continuous infusion and 25 mg/kg of loading dose then 25 mg/kg/day of continuous infusion for treatment of MRSA and Enterococcus spp infection with a MIC of ≤ 1 mg/L, respectively. The appropriate maintenance dose for MRSA and Enterococcus spp were 20 and 25 mg/kg/day divided 6 to 24 h of intermittent infusion, respectively. The recommended maintenance dose should be administrated stratified by renal function as follows; 20 mg/kg/day for patient with CrCl < 60 ml/min, 25 to 30 mg/kg/day for patient with CrCl ≥ 60 ml/min, respectively. Conclusions: The population pharmacokinetics and PK/PD analysis based on Monte Carlo simulation procedures could be used to create vancomycin dosage regimen in critically ill patients. In this study, the doses ranged from 20 to 25 mg/kg/day were recommended to treat Enterococcus spp and MRSA infection.